Synthesis and characterization of rhenium(iii) complexes with (Ph2PCH2CH2)2NR diphosphinoamine ligands - Salvarese, Nicola; Refosco, Fiorenzo; Seraglia, Roberta; Roverso, Marco; Dolmella, Alessandro; Bolzati, Cristina (Dalton Transactions, 2017)
The reactivities of diphosphinoamine ligands [(Ph2PCH2CH2)2NR] toward rhenium(iii,v) precursors have been studied. The obtained complexes have been fully characterized.